Optimization of ozone concentration and storage time in green asparagus (Asparagus officinalis L.) using response surface methodology - Pretell-Vásquez, Carla; Márquez-Villacorta, Luis; Siche, Raúl; Hayayumi-Valdivia, María (Vitae, 2022)
Background: Asparagus (Asparagus officinalis L.) green is a vegetable with a great demand worldwide, and likewise, it is highly perishable due to its high respiration rate that accelerates its senescence. Disinfection of vegetables after their harvest is an obligatory practice that can reduce losses by decomposition due to the attack of microorganisms. Therefore, it is vital to preserving its microbiological and sensory characteristics to reach the final consumer. Objective: To evaluate the effect of gaseous ozone (0 to 10 ppm) and storage time (0 to 30 days) on phenol content, overall appearance, count of molds, psychrophilic bacteria, and viable mesophilic aerobes. Methods: the response surface methodology was used, applying a rotatable central composite design. Results: The results indicated that there was a significant influence (p <0.05) of the independent variables on the characteristics studied, as well as an adequate lack of fit of the quadratic regression model (p> 0.05). By means of the contour superposition technique, it was determined that the optimal conditions for the highest retention of phenol content (16.99 mg/g) and overall appearance (7.61 points) and lower counts of viable aerobic mesophilic bacteria (5.3 x 103 CFU/g) they corresponded to 10 ppm of gaseous ozone up to 25.91 days of storage, with adequate quality characteristics in the shoots. Conclusion: the region of interest was determined for optimal retention of phenol content and overall appearance, and a lower count of viable aerobic mesophilic bacteria in green asparagus during postharvest, suggesting to use the initial application of ozone gas at 10 ppm allowing 25.9 days storage at 1 °C. The results indicate that this technology is a good alternative in the conservation of fresh vegetables.